Sistem Pengendalian Suhu Dan Kelembaban Pada Mesin Pengering Kertas - Darjat, Darjat (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
An effective and efficient paper drying tool for printing industry is very important. Utilize of this tool is to dry the paper will be printed to get a dry paper that have ideal temperature and humidity level. With the result that will make easier the process of production and to get the optimal quality of printed result.Focus of this Final Report is to design data acquisition humidity level and temperature system control to the paper drying machine based on fuzzy logic control using Atmega 8535 microcontroller, in order to get the paper that have ideal temperature and humidity level is about 33oC – 35.5oC and 41% of water content in 0.00075 inch of thickness for each of the sheet later (Perry’s Chemical Engineers’ Handbook: 12.34) 10].Observation result of fuzzy logic control in paper drying system show that bigger reference of temperature offered to the system so that the time to reach steady state condition will be more longer, where the initial condition of temperature at the same value. To get the dry ideal paper result, the setting reference of temperature that appropriate is 50oC, where the drying process with 50oC reference is resulted the paper with 38.0oC temperature and 40.9% of humidity.Keyword: Paper drying system, Fuzzy logic control, ATMega 8535 microcontroller